THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND AUDIT REPORT LAG: EVIDENCE FROM INDONESIAN - Toto Rusmanto , Margareth Herlina (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study examines audit report lag in the context of Indonesia Stock Exchange where the regulator has been established the good corporate governance program. Audit report can affect the timeliness of accounting information releases. Delays to publishing an audit report will affect many aspects such as the value of information which may cause a bad sign of companies’ conditions. The objective of this research is to examine the relation between corporate governance and audit report lag in Indonesian publicly listed companies. The data was extracted from annual reports collected from the Indonesia Stock Exchange for the year 2013. Multiple regression and statistical tests were used in the data analysis method. The research found that audit committee size and board size have a significant relationship towards audit report lag-in a negative direction; whereas, audit committee independence, audit committee meetings, audit committee expertise independent commissioners have an insignificant relationship toward audit report lag in a negative direction.